Fast Evidence-based Information Fusion - Mönks, Uwe; Lohweg, Volker (4th Internation Workshop on Cognitive Information)
Information fusion systems are crucial for the success of the upcoming fourth industrial revolution. In this emerging field, cyber-physicals systems play a major role. These are physical processing systems equipped with sensory devices which interconnect over communication networks for distributed cognitive information processing applications. Cyber-physical systems are generally limited in computational resources. Due to this fact, signal processing algorithms cannot be implemented one-to-one. Instead, efforts must be spent in algorithm optimisation towards resource efficiency and reduced computational complexity. In this contribution, we present our optimisation approach by matrix decomposition of an evidence-based conflict-reducing fusion approach which after optimisation is applicable in resource-limited devices for cognitive signal processing. We evaluate the results by comparison with the algorithm's original definition and show the improvements achieved.